The Impact of Institutional Governance on Environmental Sustainability of Energy through Economic and Social Sustainabilit - Fariba Riahi; Shams-alsadat Zahedi; Gholam Ali Farjadi; Saied Najafi (فرایند مدیریت و توسعه, 2019)
The purpose of this paper is to identify the most important components affecting energy sustainability and to study the relationship among energy sustainability dimensions by taking an institutional approach. Hence, this study aims to reach a framework through synthesizing Williamson’s institutional hierarchy and the causal relational framework of IAEA/IEA. In order to collect data, a sample of 110 out of 196 developed and under-developed countries was selected. Using partial least squares method, the most important components and interrelationships among institutional, economic, social and environmental sustainability were analyzed. The results of path analysis show that both informal institutions, such as social capital, and formal institutions, like good governance, institutional environment and market institution have positive influence on economic, social and environmental sustainability of energy systems. Also, the effects of economic sustainability on social sustainability and the effects they both have on environmental sustainability are positive and significant. In other words, enhancing all aspects of institutional, economic and social sustainability with different degrees contributes to the improvement of environmental sustainability at national and international levels.